Peningkatan Hasil Belajar dan Karakter Gotong Royong Siswa Kelas 2 SDN 07 Panjang - Dewi Yanti Gulom; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to evaluate the effectiveness of the application of Problem-Based Learning methods (Problem-Based Learning or PBL) in improving learning outcomes and mutual cooperation character of students in Grade 2 SDN 07 Panjang. The background of this study is based on The Independent curriculum that emphasizes strengthening the profile of Pancasila students, including the dimension of mutual assistance that is very relevant to social life in Indonesia. However, the implementation of The Independent curriculum in SDN 07 Panjang faces challenges, such as limited facilities and the need for training for teachers. These challenges can affect the formation of mutual cooperation characters in students as well as their academic learning outcomes. In this study, theories related to learning outcomes, Catholic Religious Education, and Problem-Based Learning Methods (PBL) are used as a basis for designing learning that can improve learning outcomes and mutual cooperation characters. Theoretical foundations such as Piaget's cognitive theory, Skinner's behavioristic theory, and Vygotsky's constructivism help to understand the mechanisms of effective learning. In addition, The Independent curriculum applied in Catholic Religious Education in Phase A supports the use of PBL to build student character, especially mutual aid. Through previous research, it was found that PBL was able to improve students ' social skills and learning outcomes. Studies by Nurhayati (2019) and Lestari (2017) show that the application of PBL in Catholic Religious Education subjects successfully improves understanding of religious teaching materials, student participation, and mutual cooperation characters. This study used the method of class action (CLA) which was carried out in two cycles. Each cycle includes a 105-minute opening, core, and closing activity. Subjects were 26 students of Grade 2 SD Phase A. Data were collected through observation and learning outcomes tests. The results showed that the application of PBL method significantly improved students ' cognitive learning outcomes and strengthened the character of mutual cooperation. In Cycle 2, there was an increase in student participation in group activities and understanding of the material.